2014
DOI: 10.1093/jnci/dju097
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-Stimulating Hormone, Thyroglobulin, and Thyroid Hormones and Risk of Differentiated Thyroid Carcinoma: The EPIC Study

Abstract: High Tg levels precede by up to 8 years the detection of TC, pointing to a long sojourn time of the disease. Low TSH levels may predispose to TC onset. Neither marker has sufficient accuracy to be a screening test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
91
3
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 101 publications
(109 citation statements)
references
References 29 publications
10
91
3
5
Order By: Relevance
“…10 The present study confirms that the simultaneously increased levels of both Tg and TSH are not useful in predicting thyroid malignancy in the preoperative period. By contrast, Tg levels were significantly lower in patients with DTC.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…10 The present study confirms that the simultaneously increased levels of both Tg and TSH are not useful in predicting thyroid malignancy in the preoperative period. By contrast, Tg levels were significantly lower in patients with DTC.…”
Section: Discussionsupporting
confidence: 68%
“…Some studies showed an increased risk of malignancy in a thyroid nodule with high serum TSH, 6,7,30,31 whereas others reported no relationship. 10,[33][34][35] In a meta-analysis including over 5000 cancer preoperatively, an increased level of serum Tg or TSH appear w not to be useful to predict malignant thyroid disorders. However, TSH:Tg ratio was found to be significantly increased in patients with thyroid cancer but it was not shown to be an independent predictor.…”
Section: Discussionmentioning
confidence: 99%
“…Although hypothyroidism and hyperthyroidism have been hypothesised to be associated with thyroid cancer risk, the evidence has been somewhat inconsistent 28 29. Low thyroid stimulating hormone levels are thought to be associated with future thyroid cancer risk;30 however, laboratory studies in rats found that malathion was associated with increased thyroid stimulating hormone secretion 31. In agricultural areas, nitrate exposure via diet and drinking water has been associated with thyroid cancer and hypothyroidism;32 we were not able to control for nitrate intake in our analyses.…”
Section: Discussionmentioning
confidence: 88%
“…Some studies have found that alcohol intake have an effect on thyroid volume, thyroid function and the responsiveness of hypothalamic-pituitary-thyroid axis [6062], which subsequently lead to the change of peripheral thyroid hormone concentrations. However, the influence is elusive with regarding to the peripheral thyroid hormone concentrations on thyroid cancer risk [6365]. Third, alcohol could also potentially influence thyroid cancer risk by altering sex steroid hormone levels [6668].…”
Section: Discussionmentioning
confidence: 99%